Quantification and characterization of primary biological aerosol particles and microbes aerosolized from Baltic seawater - J. Zinke; J. Zinke; J. Zinke; G. Pereira Freitas; G. Pereira Freitas; R. A. Foster; P. Zieger; P. Zieger; E. D. Nilsson; E. D. Nilsson; P. Markuszewski; P. Markuszewski; et al. (Atmospheric Chemistry and Physics)
Primary biological aerosol particles (PBAPs) can influence the climate and affect human health. To investigate the aerosolization of PBAPs by sea spray aerosol (SSA), we conducted ship-based campaigns in the central Baltic Sea near Östergarnsholm in May and August 2021. Using a plunging-jet sea spray simulation chamber filled with local seawater, we performed controlled chamber experiments to collect filters and measure aerosols. We determined the abundance of microbial cells in the chamber air and seawater using staining and fluorescence microscopy, normalizing these values to sodium concentrations to calculate enrichment factors. Our results showed that microbes were enriched in the aerosol by 13 to 488 times compared to the underlying seawater, with no significant enrichment observed in the sea surface microlayer. Microbial abundances obtained through microscopy were compared with estimates of fluorescent PBAPs (fPBAPs) using a single-particle fluorescence spectrometer. We estimated microbial emission fluxes using two independent approaches: (1) applying the enrichment factors derived from this study with mass flux estimates from previous SSA parameterizations and (2) using a scaling approach from a companion study. Both methods produced microbial emission flux estimates that were in good agreement and of the same order of magnitude as previous studies, while fPBAP emission flux estimates were significantly lower. Furthermore, 16S rRNA sequencing identified the diversity of bacteria enriched in the nascent SSA compared to the underlying seawater.